Impact of stent diameter on outcomes following percutaneous coronary intervention with second‐generation drug‐eluting stents: Results from a large single‐center registry. Issue 3 (6th September 2019) - Plitt, Anna; Claessen, Bimmer E.; Sartori, Samantha; Baber, Usman; Chandrasekhar, Jaya; Aquino, Melissa; Vijay, Pooja; Elsayed, Sherif; Kovacic, Jason C.; Sweeny, Joseph; Barman, Nitin; Moreno, Pedro; et al.
Abstract: Background: In patients treated with bare metal stents and first‐generation drug‐eluting stents (DES) smaller stent diameter (SD) has been associated with worse long term outcomes after percutaneous coronary intervention (PCI). Data on the impact of small SD on outcomes after PCI with second‐generation DES is scarce. Methods: Consecutive patients treated with second‐generation DES between 2010 and 2016 were included in a single tertiary center. Patients were grouped according to SD: ≤2.50 mm, 2.75 ≤ 3.00 mm, 3.25 ≤ 3.50 mm, and >3.50 mm. One‐year event rates were estimated using the Kaplan–Meier method and adjusted hazard ratios were generated using Cox regression analysis. The primary endpoint was major adverse cardiac events (MACE; death, myocardial infarction [MI], or target vessel revascularization [TVR]). Results: Of the 17, 607 patients who underwent PCI with second‐generation DES, 32.6% ( n = 5, 741) had SD ≤2.5 mm, 39.1% ( n = 6, 890) had SD 2.75 ≤ 3.0 mm, 22.2% ( n = 3, 910) had SD 3.25 ≤ 3.5 mm, and 6.1% ( n = 1, 066) had SD >3.5 mm. At 1 year, MACE rates were 10.5%, 9.5%, 8.0%, and 8.0%, respectively, with increasing SD ( p = .006). TVR rates decreased with increasing SD (7.2%, 5.8%, 4.7%, and 3.3%, respectively [ p < .0001]) whereas rates of MI across SD groups were comparable (1.7%, 1.9%, 2.0%, and 1.5%, respectively [ p = .60]). After multivariable adjustment, smaller SD remained associated with higher rates of MACE, TVR, and target lesion revascularization. Conclusion: In a large cohort of patients undergoing PCI with second‐generation DES, smaller SD was associated with increased MACE, driven by higher rates of repeat revascularization. Further research into the optimal treatment of small coronary arteries is warranted.